Website learning media development in the subject of pancasila education students of class iia of elementary school pengadegan 07 south jakarta - Ritonga, Rudi; dwika, Dwika (Jurnal Pendidikan PKN (Pancasila dan Kewarganegaraan), 2025)
This research aims to develop website learning media for the subject of Pancasila Education of Class IIA Students of SDN Pengadegan 07 South Jakarta. The method in this research is Research and Development (R&D), Dick and Carey development model with 10 stages used. This media was tested by several experts, namely media, language experts, material experts, students and teachers of class IIA. Data collection was done through interviews and observations. Validation results media by media experts get 85% with very valid qualifications, material experts on this media obtaining a very valid qualification with a percentage of 92%, language experts in this media obtained percentage 88%. In addition to validation by experts, website media has been implemented on teachers and students of class IIA SDN Pengadegan 07 South Jakarta. The results of this study show that development of website learning media for Pancasila Education subjects for grade students IIA at SDN Pengadegan 07 South Jakarta is suitable for use by teachers and class II students of the School Base